2015
DOI: 10.1007/s10753-014-0101-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-nociceptive Actions of Systemically or Locally Treated Adipose-Derived Mesenchymal Stem Cells in Experimental Inflammatory Model

Abstract: Cell-based therapies using mesenchymal stem cells provide hopeful results. Therefore, in this present study, possible anti-inflammatory and anti-nociceptive actions of locally or systemically treated adipose-derived mesenchymal stem cells (ADMSCs) investigated in experimental inflammation model. ADMSCs were isolated from a male Wistar rat under anesthesia, and then they were cultured and expanded for transplantation in all the experimental animals. Effects of intraperitoneal or intraplantar ADMSC treatments on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Nonetheless, the long-term use of NSAIDs is not recommended for a variety of patients, warranting the development of valid therapeutic alternatives, such as MSCs recently used for their anti-inflammatory and antinociceptive activity in an experimental inflammatory model (44). In the present study, neonatal MSCs were evaluated as an alternative to NSAIDs in the management of the pain and walk recovery of dogs operated using TPLO for CrCL rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the long-term use of NSAIDs is not recommended for a variety of patients, warranting the development of valid therapeutic alternatives, such as MSCs recently used for their anti-inflammatory and antinociceptive activity in an experimental inflammatory model (44). In the present study, neonatal MSCs were evaluated as an alternative to NSAIDs in the management of the pain and walk recovery of dogs operated using TPLO for CrCL rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al in 2015 have demonstrated that Mesenchymal stem cells could attenuated inflammatory cytokines such as TNF- α , IL-17, IL-23, etc and promote the expression of TGF- β which is result in modulating the inflammation ( 18 ). Also related to anti-inflammatory character of MSCs, Mert et al in 2015 have investigated that the locally transplanted MSCs could suppress the level of IL-6 and (IL)-1 β and enhance IL-10 this effects of MSCs on these cytokines results in decreasing the inflammation ( 19 ). In addition above studies, Gu et al in 2014 showed that the expression levels of TNF- α , IL-1 β mRNA and P-I κ B- α , P-IKK β , p53 protein were significantly decreased and I κ B- α , Bcl-2 protein expression levels were significantly increased after brain stroke and mesenchymal stem cell transplantation ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…PMF exposure system and application procedures to rats were performed as previously described [Mert et al, , ]. Briefly, PMF exposure system was generated in a pair of Helmholtz coils 60 cm in diameter (placed 30 cm apart), with 100 turns of 18 gauge copper wire in a Faraday cage.…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, cell‐based therapy can also be a capable approach for chronic neuropathic pain. Adipose tissue has been recently preferred as a suitable source of MSCs because it can be harvested easily from subcutaneous fat tissue [Mert et al, ]. Adipose tissue‐derived mesenchymal stem cells (ADMSC) have similar differentiation potentials and immunosuppressive capabilities to MSC derived from bone marrow [Strem et al, ].…”
Section: Introductionmentioning
confidence: 99%